Nationalism and the Economy : Explorations into a Neglected Relationship - Fetzer, Thomas, 1974-; Berger, Stefan (Book collections on Project MUSE., 2019)
This book is the first attempt to bridge the current divide between studies addressing 'economic nationalism' as a deliberate ideology and movement of economic 'nation-building', and the literature concerned with more diffuse expressions of economic 'nationness' - from national economic symbols and memories, to the 'banal' world of product communicationThe editors seeks to highlight the importance of economic issues for the study of nations and nationalism, and its findings point to the need to give economic phenomena a more prominent place in the field of nationalism studies. The authors of t.